PENGEMBANGAN PERANGKAT PEMBELAJARAN GENERATIF UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR MATEMATIS TINGKAT TINGGI SISWA SMP - Moma, La; Tamalene, Hanisa; Rumalean, Samad (Jurnal Pendidikan Matematika Unpatti, 2023)
The current characteristics of learning mathematics are more focused on procedural abilities, one-way communication, monotonous class settings, low-order thinking skills, depending on textbooks, more dominant routine questions, and low-level questions. Teachers rarely give high-order thinking skills to students in learning mathematics, so students are given non-routine questions, and questions that require critical and creative solutions, students have difficulty solving them. To overcome this, this study used a generative learning model. Learning with this model has succeeded in increasing student mathematics learning outcomes. The specific objective of this research is to develop generative learning tools to improve the high-level mathematical thinking skills of junior high school students. This research is product development research in the form of generative learning tools to improve higher-level mathematical thinking skills to be used in junior high schools. There are three learning tools developed, namely teaching materials, student worksheets, and learning implementation plans, which will be used in the teaching and learning process. The development of this learning device refers to the general teaching material development model of Tjeerd Plomp (1997) which consists of several phases, namely: (1) initial investigation phase; (2) design phase; (3) realization; and (4) test, evaluation, and revision phases. From the research conducted, it was found that the creative learning model developed in this study met the criteria of validity, practicality, and effectiveness